HIPOTESIS SOBRE FACTORES DETERMINANTES DE DIMORFISMO SEXUAL EN SPHEX LATREILLEI LEP. (HYMENOPTERA: SPHECIDAE) - Toro, Haroldo; Chiappa, Elizabeth (Acta Entomológica Chilena, 2022)
Observations made on the external morphology and reproductive behavior of Sphex latreillei Lep. point out a sexual dimorphism in size, color of the IV metasomal segment and a number of behavioral characters like the use of perchs by the males, chasing of flying objects, patrolling a limited area and sleeping in cióse groups on the tops of trees. It is hypothetised that the larger males are selected mainly by intrasexual selection. There is a high correlation between size and number of copulations in males; the smaller specimens are chased away from the nesting area, but they are always present in the population, which is probably due to an alternative pairing strategy in the marginal zone of the reproductive area. They may resull from inadecuate nutrition at the larval stage or the haplo-diploid mechanism of sex determination. The haplo-diploid system suggests an hypotesis on the origen of sexual reproduction.